The Motivation Processes of MA in English Applied Linguistics Students - Kövér, Ármin; Szűcs, Ágota (Working Papers in Language Pedagogy, 2015)
Research into L2 motivation has more than five decades of tradition. Despite the copious data, information about the motivation processes of MA students is still very sparse. Therefore, the aim of this article is (1) to explore the characteristics of the general motivation of English MA students and (2) to examine the phenomenon as a dynamically changing construct. It is a small-scale qualitative exploratory study involving six English Applied Linguistics MA students: two first-year and two second-year students and two graduates. In order to investigate the motivation of these students semi-structured interviews were administered. The results suggest that the motivation of the participating students is a highly complex phenomenon compounded of several different elements and that the interaction of these elements can be examined on two levels; namely, the motivation process on a daily basis and the motivation process over a number of years.